Exploring Students’ Perceptions of Portfolio-Based Assessment in English Language Learning: Insight from an ELT Classroom Context - Fitriyani, Fitriyani; Miranty, Delsa (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2025)
This study explores students’ perceptions of portfolio-based assessment (PBA) in English language learning in ninth-grade students who utilize PBA as an assessment tool in their English studies. It focuses on its benefits, challenges, and overall effectiveness. The study uses a qualitative method. The data were collected through questionnaires distributed to 40 students and semi-structured interviews with two participants. The result demonstrates that most students recognize the benefits of PBA in tracking progress and fostering independent learning. However, difficulties were also noted, including time-consuming portfolio administration, unclear grading standards, and the need for additional guidance. Three main themes- self-monitoring, responsibility, and self-support in learning were found using theme analysis of the interview answers. Although 75% of students were satisfied with PBA, the surveys imply that digital technologies, well-defined criteria, and organized advice could improve efficiency. Despite its difficulties, PBA offers an engaging and reflective learning environment that lets students participate actively in their education. The study found that PBA positively impacts students' learning improvement, promoting learner autonomy and academic development.